AN EARNED VALUE MANAGEMENT (EVM) FRAMEWORK FOR THE PERFORMANCE MEASUREMENT OF PFI CONSTRUCTION PROJECTS IN MALAYSIA - Ali Khan, M Waris; Khamidi, M. Faris; Idrus, Arazi (2010)
Earned Value Management (EVM) is a project performance measurement method which integrates the cost, schedule and technical performance. It establishes the earn value of a completed work and compares it with the actual cost and planned cost to determine the project performance and to forecast its future trends. This technique encourages public and private organizations to monitor the performance of their mega projects effectively. The present study examines the EVM process in order to derive a framework for monitoring and controlling of PFI construction projects in Malaysia. The proposed framework is comprised of five fundamental elements i.e. organizational policy; planning; implementation; measurement, analysis and reporting; and management performance review. These elements interact with each other to form an integrated EVM performance measurement system. The aim of this framework is to provide the construction organizations an understandable view about the implementation of an EVM System.